Intergenerational Neuroimaging of Human Brain Circuitry. Issue 10 (October 2016) - Ho, Tiffany C.; Sanders, Stephan J.; Gotlib, Ian H.; Hoeft, Fumiko
Abstract : Neuroscientists are increasingly using advanced neuroimaging methods to elucidate the intergenerational transmission of human brain circuitry. This new line of work promises to shed light on the ontogeny of complex behavioral traits, including psychiatric disorders, and possible mechanisms of transmission. Here we highlight recent intergenerational neuroimaging studies and provide recommendations for future work.